Financial expression of forest functions value - Jiří Schneider; Petr Kupec; Ilja Vyskot; Katarína Domokošová; Alice Melicharová (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The financial expression of forest functions value can be based (similarly as an approach to forest functions) on different conceptions: anthropocentric utilitarian conception - forest and its functions are an economic estate (instrument of production) fully controlled by man, and ecosystem lifepreserving conception – forest and its functions are a life-giving source and irreplaceable component of the environment at the same time being the source of an essential renewable raw material. The ecosystem conception of forests and their functions does not consider forests as an exclusive economic estate but as a national wealth and irreplaceable component of the environment. Expression of values of forest functions through money is thus a comparable means of society to control and maintain life-giving sources and components of the environment. A method used for the financial expression of values of forest functions is “a financial explicit comparison to a socially well-known economic event”. The dominant product of a bioproduction function – wood and its financial relations – price is a socially well-known economic event from the field of forest functions. However, from the viewpoint of a known economic event, wood price in not a quite objective indicator. It is dependent on market relations and changing social demands. The generally used market principle of society, however, does not use permanent or absolute constant financial values. Value conditions, levels and scales are always topical conditions.